2018
DOI: 10.18233/apm39no2pp99-1081571
|View full text |Cite
|
Sign up to set email alerts
|

Representaciones maternas sobre salud y lactancia del hijo prematuro en hospitales con y sin certificación de Hospital Amigo del Niño y de la Madre

Abstract: ANTECEDENTES: la prevalencia de la lactancia materna en prematuros mexicanos es baja, a pesar de ser una medida accesible y de bajo costo recomendada por la Organización Mundial de la Salud. Uno de os factores de abandono es la percepción de baja producción láctea. OBJETIVO: comparar las representaciones maternas de salud y lactancia en hijos prematuros internados en hospitales de referencia, en tanto certificado o no como Hospital Amigo del Niño y de la Madre.MATERIAL Y MÉTODOS: estudio cualitativo efectuado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Although also among the reasons to abandon breastfeeding is the medical prescription to suspend it. [13] Currently, the Mexican clinical guidelines for enteral feeding of preterm infants of 32 weeks or less of gestational age include the use of formulas for preterm infants. [12] This is part of the challenges for BFHI hospitals and health personnel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although also among the reasons to abandon breastfeeding is the medical prescription to suspend it. [13] Currently, the Mexican clinical guidelines for enteral feeding of preterm infants of 32 weeks or less of gestational age include the use of formulas for preterm infants. [12] This is part of the challenges for BFHI hospitals and health personnel.…”
Section: Discussionmentioning
confidence: 99%
“…[12] A qualitative study revealed that for mothers of preterm inpatients "health is related to the corporality of the preterm infant", thus, weight represents the key to health. [13] A Brazilian cohort of 42 preterm infants with 40 weeks of corrected age and with assessment at different cut-off points for home follow-up (at 15 and 45 days after hospital discharge, at the third and sixth month of life), studied the prevalence of types of feeding and weight gain. At 15 days the EBF had the highest peak (71.5%), followed by MBF (19%) and finally, AF (9.5%) and the average daily weight gain in preterm infants was 18.16 g, 13.37 g and 21.17 g per day for EBF, MBF, and AF respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[12,14] In a qualitative study whose objective was to reveal the social representations, that is, the form of socially elaborated knowledge that generates opinions, beliefs, and meanings that are socialized and produce an impact on practices, in this case, the social representations of mothers < 20 years with a preterm infant about Exclusive Breastfeeding, findings revealed that exclusive breastfeeding represents them that they would shorten the duration or change this option for artificial feeding, for their return to school and for some beliefs such as "the child does not fill up", the child "does not digest milk well" or "milk is harmful", nevertheless they had received information about the benefits and the recommendation of a minimum duration of six months of Exclusive Breastfeeding in the hospital, and although they believed that Exclusive Breastfeeding was the best option for their child's growth. [15] However there is also the counterpart, that is, adolescent mothers do not receive guidance, orientation, or advice to start and continue with exclusive breastfeeding, this is associated with discontinuation or abandonment of Exclusive Breastfeeding. [12] In this regard, a Mexican organization the Pro-Breastfeeding Association (APROLAM) reports barriers to Exclusive Breastfeeding due to ignorance of the advantages as well as of the practical aspects to start it, [14] and the Mexican project (Official Standard PROY-NOM-050-SSA2-2018), for the promotion, protection, and support of Exclusive Breastfeeding, establishes that should be promoted especially in marginalized areas until the sixth month.…”
Section: Introductionmentioning
confidence: 99%